Effect of Current Ratio, Return on Equity, Debt to Equity Ratio, and Earnings per Share on Stock Returns of Mining Companies Listed on the Indonesia Stock Exchange - Chintya Nurmayasari; Haryono Umar; Agustina Indriani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study was conducted to analyze the development of stock values in the mining companies listed on the Indonesia Stock Exchange (IDX) using the ratio of profitability, liquidity, and debt to stock returns for 2015–2019 period. Purposive sampling technique was used for data collection with the following criteria: (1) companies listed on the IDX during the observation period (2015–2019) for consecutive years; (2) companies that continually provide financial reports during the observation period (2015-2019); (3) companies that have complete data in accordance with the research variables required in this study. Based on those criteria, the data obtained from the report published by the IDX were comprised of 15 companies as the study samples. Meanwhile, the study used panel data regression with least-squares equation and hypothesis testing using t-statistics to test the partial regression coefficients. Furthermore, f-statistics was used to test the simultaneous effect at the significance level of 5%. Based on the analysis results using software eviews version 10, it revealed that: (1) current ratio had no effect on stock return; (2) return on equity had no effect on stock return; (3) debt to equity ratio had no effect on stock return; (4) earnings per share had no effect on stock return; (5) current ratio, return on equity, debt to equity ratio, earnings per share simultaneously had no effect on stock return.